Reduction of osteonecrosis of the jaw (ONJ) after implementation of preventive measures in patients with multiple myeloma treated with zoledronic acid - Dimopoulos, M.A.; Kastritis, E.; Bamia, C.; Melakopoulos, I.; Gika, D.; Roussou, M.; Migkou, M.; Eleftherakis-Papaiakovou, E.; Christoulas, D.; Terpos, E.; Bamias, A. (Annals of Oncology, 2009)
Background: Osteonecrosis of the jaw (ONJ) is a well-described complication of bisphosphonates use in patients with multiple myeloma (MM). We investigated whether the occurrence of ONJ decreased after the implementation of preventive measures in 128 patients with MM who received zoledronic acid. Patients and methods: Patients with MM who received zoledronic acid were included in this analysis. Patients with a previous use of other bisphosphonates were excluded; patients were stratified into group A (n = 38) and group B (n = 90) if treatment was started before or after the implementation of preventive measures. Results: One hundred and twenty-eight patients were included in this analysis. Sixteen patients (12.5%) developed ONJ - group A: 8 (26.3%), group B: 2 (6.7%) (P = 0.002). The incidence rate (IR) was 0.671/100 person-months for group A and 0.230/100 person-months for group B [IR ratio 2.92, P = 0.029, 95% confidence interval 1.06-8.03]. No patient in group B developed stage III ONJ. Conclusion: In conclusion, the risk of developing ONJ after treatment of zoledronic acid is reduced (but not deleted) by the implementation of preventive measures. © The Author 2008. Published by Oxford University Press on behalf of the European Society for Medical Oncology. All rights reserved.
Keywords: multiple myeloma; Osteonecrosis; Preventive measures; Zoledronic acid